ABOUT ABDAL ONOMASTIC UNIT - Rahila Hummatova (World Scientific Reports, 2023)
The study of the onomastic lexicon, which is an important part of the vocabulary of the Azerbaijani language, is extremely valuable in terms of studying the laws of development of the Azerbaijani language, the formation and development tendencies of the literary language, the material history, ethnogenesis, and traditions of the people. A. Gurbanov, who had irreplaceable services in the foundation, formation and formation of the science of onomalogy of Azerbaijan, wrote about it: "The importance of onomastic research in order to expand the horizons of linguistics and ensure its comprehensive development is very great at present. In-depth research, careful analysis and scientific summarization of the onomastic lexicon, which has a special place in the vocabulary of the language, helps to reveal many complex and necessary issues of the language and history of our people. Therefore, to approach onomastic materials from a scientific point of view, to provide an accurate and fundamental analysis of it is one of the urgent and necessary issues. (9,5) A. Gurbanov called special names in the lexical system of the language onomastics, and the branch of linguistics that deals with special names is called onomalogy. Starting from the 80s of the 20th century, the special weight of linguistic studies devoted to the study of the onomastic system of our language has increased significantly, and the interest in this field has led to the writing of dozens of monographs.